Organophosphorus flame retardants (PFRs) and plasticisers in harbour porpoises (Phocoena phocoena) stranded or bycaught in the UK during 2012. Issue 1 (15th September 2015) - Papachlimitzou, Alexandra; Barber, Jonathan L.; Losada, Sara; Bersuder, Philippe; Deaville, Rob; Brownlow, Andrew; Penrose, Rod; Jepson, Paul D.; Law, Robin J.
Highlights: Organophosphorous flame retardants have been analysed in blubber and liver of stranded harbour porpoises. Only 6 out of 20 measured compounds were detected in the samples. Levels were much lower than those found previously for PBDEs and HBCD in harbour porpoises. Abstract: A suite of twenty organophosphorus flame retardant compounds have been determined in blubber and liver tissue of twenty harbour porpoises stranded or bycaught in the UK during 2012 in order to establish current levels of contamination. Fourteen of the twenty compounds were below the limits of quantification in all samples. Six could be quantified at maximum concentrations (in blubber) between 6.7 and 246 μg kg −1 wet weight. These levels do not suggest a high level of concern regarding potential impacts and do not indicate that routine monitoring in UK porpoises is warranted at this time.